KONTRIBUSI ULAMA JAWA DALAM MEMBUMIKAN HUKUM ISLAM - Sari, Linda Anastyapatika; Imawan, Dzulkifli Hadi (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This article reviews the historical study of Demak Bintoro kingdom, which was the first Islamic kingdom on the Island of Java, located in the city of Demak, Central Java with its heday during the leadership of the Treanggana sultan. The founding of this kingdom was marked by the collapse of Majapahit kingdom. The research method used in this research method used in this research is qualitative with a historical approacrh, and the data collection techniques is using literature which is then analyzed using descriptive analysis tehory. The results obtained are taht as the first kingdom on the Island of Java, the dynamic development of Islamic law that occured in the Demak Bintoro kingdom invloved several a famous cleric in Java who in his approach process used socio cultural theory by acculturating Islamic law with the culture that had prevailed in previous societies such as that found in shadow puppet art performance, tombo ati songs, and so on. Keywords: Javanese Ulama, Islamic Law, Demak Bintoro Kingdom